Coated stainless steel archwires' discoloration measured by computerized system (An in-vitro study) - Abeer B Mahmood (College of Dentistry/ University of Baghdad, 2020)
Background: Aesthetic archwires are used to overcome the aesthetic problems of stainless steel wires but the color of the coating layer can be changed with time when exposed to oral environments. The aim of this study was to evaluate the degree of color change of different aesthetic archwires from different companies under different coloring solutions. Materials and Methods: One hundred fifty samples of coated archwires from three companies (Highland, G&H and Dany) were immersed in 5 solutions (artificial saliva, turmeric, tea, coffee and Miranda) to evaluate the degree of color changes after 7, 14 and 21 days using visible spectrophotometer. Data were collected and analyzed using one way ANOVA and post hoc Tukey's tests. Results: Turmeric solution caused high color change than other solutions. Aesthetic archwires from Highland company showed the highest degree of color change than archwires from other companies. Conclusions: Turmeric solution produced more discoloration than other solutions and the effects of these solutions are related to different chemical compositions of those solutions.